IMPLEMENTASI KEBIJAKAN KEPENDUDUKAN DI KABUPATEN KUANTAN SINGINGI (STUDI KASUS PENGURUSAN AKTA KELAHIRAN TAHUN 2012) - Aryanti, Elina; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Under the Law No. 23 of 2006 in Article 27 paragraph 1 explained that everybirth must be reported to the institution birth registration in birth place of occurrence ofthe event no later than 60 (sixty) days after birth. But in reality there are many people inthe district Kuantan Singingi not have a birth certificate. Therefore, the authors intend toconduct research in order to determine how the implementation of population policies inthe District Kuantan Singingi (Kuantan Singingi Regional Regulation No. 12 of 2011 onthe Implementation of Administration) and how public support for government policiesregarding the administration, especially processing of birth certificates in the DistrictKuantan Singingi in 2012 and the factors that influence it.This research sites in the district Kuantan Singingi. This study includesqualitative research, the technique of collecting data through interviews, observation,and research informants determined by purposive sampling technique. In this research,the theory is derived from the theory put forward by Grindle, the successfulimplementation of these policies can be seen from the benefits that would result,deployed resources, compliance and responsiveness to the program.The results of this research concluded that the implementation of governmentpolicy Kuantan Singingi about obtaining a birth certificate has not been run inaccordance with the expected goals and many people who do not support thegovernment's policy in regard to obtaining a birth certificate. Population and CivilRegistration Department to further improve the dissemination of the program's birthcertificate and improve service quality Population Administration again, because it isthe right of people to be provided with good.Keywords: Policy Implementation, Community Support, Birth Certificates